Analysis of media use and creation of virtual communities concerning the #Frena case in Mexico - López Robles, Adalberto (2023)
The exchange of news on social networks has become a new source of income for the media. In this regard, it is argued that traditional media have had to adapt to the new reality to survive in the new media environment where they compete with news portals. This proliferation of media has allowed citizens to have more options to choose the news of their choice. Under the assumption that voters' preferences for related media affect the editorial lines of the media, the article investigates what type of media, traditional or digital, is more likely to satisfy the demands of readers. To answer this question, data extracted from Twitter about the #Frena case in Mexico is used. The modeling and visualization of the same were done in the RStudio program. The findings suggest that users tend to share media hyperlinks that are ideologically closer to their political beliefs and that digital media are more likely than traditional media to produce content for segmented audiences. These results seek to contribute to empirical research on media and audiences in digital environments.